Rapid method for DNA isolation from a tough cell wall green alga Tetraspora sp. CU2551 - Maneeruttanarungroj, Cherdsak; Incharoensakdi, Aran (My University, 2016)
Genetic studies are important to understand the complex biological system of various organisms. Some eukaryotic green organisms have tough cell wall which precludes the efficient extraction of the genetic materials. Here, we developed the method for simple and rapid isolation of high quality DNA from a green alga Tetraspora sp. CU2551. The cell homogenization procedures were combined with physical force plus heat treatment to disrupt the cell envelope of Tetraspora sp. CU2551. Without protease treatment, vortexing with glass bead for 30–105 s at 70 °C led to the isolation of a high purity DNA which was suitable for downstream process. The improved method was successfully developed and could be applied for the rapid isolation of DNA from other unicellular and filamentous green microalgal strains.
Keywords: Green algae; Rapid DNA isolation; Tetraspora